Technique of definition of eccentricity of an orbit of the planet - Kulik V. I., Kulik I. V. (Interactive science, 2016)
the technique of definition eccentricity orbits only by measurement of angular position of a planet is offered.
Keywords: время; орбита; линия апсид; линия параметров; средняя аномалия; истинная аномалия; уравнение центра; луч времени; time; orbit; the line of apses; the line parameters; mean anomaly; the true anomaly; the equation of the center; evenly rotating beam time